Influence of chlorides on magnesium sulphate attack for mortars with Portland cement and slag based binders. (30th November 2017) - Maes, Mathias; De Belie, Nele
Highlights: Influence of Cl − on MgSO4 attack is temperature and binder type dependent. Cl − aggravates MgSO4 attack when blast-furnace slag is used. At 5 °C chlorides in MgSO4 environment increase deterioration regardless binder type. At 5 °C thaumasite degradation in presence of Cl − and MgSO4 is severe in all cases. Abstract: Sulphate containing environments are aggressive and cause damage to cementitious materials by means of cracking, spalling and strength loss. In realistic conditions, sulphates may be found in combination with e.g. chlorides. Therefore, to predict concrete's durability, it is important to understand the (combined) attack mechanisms and estimate their effect. This study aimed to elucidate especially the influence of chlorides on magnesium sulphate attack at two different relevant temperatures (5 °C and 20 °C) and for mortars with different binders, including ordinary Portland cement (OPC), high-sulphate resistant Portland cement (HSR) and a binder composed of 50% blast-furnace slag (BFS) and 50% ordinary Portland cement. Mass change measurements were performed to examine the influence of Cl − on MgSO4 attack, and XRD-analyses to identify phase changes. It can be concluded that the influence of Cl − on MgSO4 attack is temperature and binder type dependent. The presence of chlorides does not affect deterioration due to magnesium sulphate for OPC and HSR at an environmental temperature of 20 °C, however, it increases the degradation when BFS is used as partial binder and/or when temperature decreases to 5 °C. The presence of BFS decreases the formation of a protecting brucite layer and favours decomposition of calcium silicate hydrates to magnesium silicate hydrates. At 5 °C the degradation involves thaumasite formation, and is more equal for the different binders and quite severe.